Greenhouse gas emission and cadmium contamination in rice paddies: research progresses in trade-off relationships, influencing factors and synergistic mitigation measures - Qi, Gaoxiang; Liu, Hongyuan; Dong, Hongyun; Zhang, Yan; Wang, Yanjun; Wang, Hongcheng; Li, Xinhua (Frontiers in Sustainable Food Systems, 2025)
Rice paddies, critical for global food security, confront dual challenges of greenhouse gas (GHG, e.g., CH4, N2O) emissions and cadmium (Cd) contamination. This review systematically summarizes their trade-off relationships, influencing factors, and synergistic mitigation measures. The trade-off is primarily driven by soil redox potential (Eh) fluctuations under alternating flooding-drying. Flooding reduces Cd bioavailability but boosts CH4 emissions, while drainage lowers CH4 but increases Cd mobility. The trade-off relationship was further regulated by soil microbial interactions and rice root physiology. Key influencing factors include soil physicochemical properties such as Eh, pH, organic matter, and agronomic practices including water management, agricultural inputs and crop varieties. Synergistic mitigation strategies involve optimized water management for balancing Eh to reduce both risks, modified biochar/combined amendments for immobilizing Cd and inhibiting CH4, targeted breeding, and optimized fertilization. This review provides a multi-scale framework linking mechanisms to practical management, emphasizing the need for integrated strategies to achieve sustainable paddy production.